CRITICISM OF THE CONCEPT OF INTERTEKSTUALITY OF THE QURAN WITH JEWISH TRADITION IN ABRAHAM GEIGER'S VIEW - As’adah, Rifqi (UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
The main focus of this research is the thoughts of Abraham Geiger regarding the Al-Qur'an and Prophet Muhammad SAW. Abraham Geiger is an orientalist who has a skeptical attitude and gives a negative assessment of Prophet Muhammad SAW. Through his monumental work entitled